Aerosolized Gamma Interferon (IFN-γ) Induces Expression of the Genes Encoding the IFN-γ-Inducible 10-Kilodalton Protein but Not Inducible Nitric Oxide Synthase in the Lung during Tuberculosis - Raju, Bindu (American Society for Microbiology, 2004)
Gamma interferon (IFN-γ) is critical in the immune response against Mycobacterium tuberculosis. In an ongoing trial of aerosol IFN-γ in conjunction with standard drug therapy, we have observed activation of IFN signaling in bronchoalveolar lavage (BAL) cells from tuberculosis (TB) patients. We hypothesized that aerosol IFN-γ treatment of pulmonary TB would increase expression of genes important for the control of TB. We investigated the expression of downstream genes by measuring inducible nitric oxide synthase (iNOS) and the chemokine IFN-inducible 10-kDa protein (IP-10) by real-time quantitative reverse transcription-PCR. In vitro, M. tuberculosis induced IP-10, and IFN-γ stimulated this further, with no effect on iNOS expression. We studied 21 patients with pulmonary TB and 7 healthy subjects. Similar to the in vitro model, IP-10 mRNA was increased in BAL cells from TB patients and was augmented after treatment with aerosolized IFN-γ. TB was also associated with elevated iNOS mRNA, but aerosolized IFN-γ did not further enhance expression. Genomic analysis identified 1,300 of 4,058 genes expressed in BAL cells from six TB patients before and after 1 month of therapy, including aerosolized IFN-γ. However, only 15 genes were differentially regulated by IFN-γ. We conclude that iNOS and IP-10 mRNA expression is increased in TB but that aerosol IFN-γ treatment increases expression of few genes in the human lung.